SIMULASI ANTRIAN PELAYANAN PADA GARDU TOL BINJAI - Akim Manaor Hara Pardede; Herdianta Herdianta; Suci Ramadani; Husnul Khair; Siswan Syahputra (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2019)
Services performed by service providers must be maximized, so that customers get satisfaction in receiving services. The thing that affects service maximally is the limited available resources, so more research is needed about the queuing system that has gone so far. Binjai City already has a toll road and has been operating since 2018, so far the use of toll roads is still running smoothly, but it should be noted whether this toll road has been operating optimally or not optimally. Toll roads are an important part of the transportation system, toll roads not only function as a good choice to avoid traffic congestion, but also affect all traffic conditions for the metropolitan area. Congestion is currently not a priority issue on the Binjai-Medan toll road. From the results of the research conducted, information is obtained that the number of toll gates is still appropriate, namely 3 Substations, Probability of busy Substation = <1 means that for now the Toll Gate will not be long queues at the time of normal everyday conditions, and further analysis is needed in the following years, so that the possibility of a Toll Station can always be maximized.